Pleistocene marine fish invasions and paleoenvironmental reconstructions in the eastern Mediterranean. (15th September 2018) - Agiadi, Konstantina; Girone, Angela; Koskeridou, Efterpi; Moissette, Pierre; Cornée, Jean-Jacques; Quillévéré, Frédéric
Abstract: Marine bioinvasions affect ecosystems in irreversible ways, creating socio-economic problems worldwide. In particular, eastern Mediterranean marine fish faunas today are significantly disturbed due to overfishing, habitat deterioration, the Lessepsian invasion, and climate change. Isolating the impact of each parameter is difficult, because pre-anthropogenic activity data are lacking. In this study, we use the paleontological record to infer the causes and mechanisms behind marine fish invasions, focusing on the Mediterranean basin, which is a restricted basin and a biological hotspot, where the effects of climatic and oceanographic changes are amplified. Therefore, the Mediterranean Sea is an ideal area to study marine biological invasions in relation to abrupt climate changes. Furthermore, we focus on the Pleistocene, which was a period of intense glacial–interglacial changes. Thus, we investigate the effect of climate changes on the fish fauna of an eastern Mediterranean shelf, by identifying the fish otoliths in the Early–Middle Pleistocene marine sediments of Rhodes (Greece). We offer a synthesis of the Mediterranean marine fish from the Tortonian until today and hypothesize on the conditions that drove marine fish distribution range shifts during the Pleistocene. We reconstruct the paleobathymetric evolution of the study areas based on fish otoliths, and we consider taphonomy in our interpretations. The Pleistocene climatic variability induced periodic and gradual replacements of fish taxa. Episodic invasions of cold-water North Atlantic mesopelagic species are correlated with intervals of climatic deterioration, specifically during marine isotope stages 50, 44, 36, 20, and 18. Highlights: Revised early–middle Pleistocene paleobiogeographic distributions of Mediterranean marine fish fauna. Paleobathymetric reconstruction of the NE Rhodes shelf (SE Aegean arc) for Gelasian–Ionian. Cold-water marine fish invasions in Mediterranean after 1.5 Ma. Episodic invasions correlated with cold marine isotope stages 50, 44, 36, 20, and 18. Warm-water fish final disappearance from Mediterranean during the Late Pleistocene.